2017
DOI: 10.1002/smll.201700355
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Efficient Bifunctional Ultrathin Nanosheets Array for Electrochemical Overall Water Splitting

Abstract: The design of cost-efficient earth-abundant catalysts with superior performance for the electrochemical water splitting is highly desirable. Herein, a general strategy for fabricating superior bifunctional water splitting electrodes is reported, where cost-efficient earth-abundant ultrathin Ni-based nanosheets arrays are directly grown on nickel foam (NF). The newly created Ni-based nanosheets@NF exhibit unique features of ultrathin building block, 3D hierarchical structure, and alloy effect with the optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 45 publications
1
52
2
Order By: Relevance
“…This value was larger than that for the (Pt/C)/NF electrode (60 mV), but lower than those for previously reported bifunctional catalysts, including NiFe LDH (210 mV), NiFe LDH@graphene (300 mV), Ni 5 Fe LDH (133 mV), CoO/MoO x (163 mV), sulfur‐incorporated NiFe 2 O 4 (138 mV), Ni@NiO (153 mV), and Ni 0.75 Fe 0.25 LDH (169 mV) in 1 m KOH or NaOH (Figure E). A Tafel slope of the FeCoOOH nanosheets (79 mV/dec) was larger than that of the Pt/C catalyst (44 mV/dec) (Figure F), but smaller than reported values for NiFe LDH@graphene (110 mV/dec), Ni 5 Fe LDH (89 mV/dec), and Ni@NiO (84 mV/dec) . The high HER activity of the FeCoOOH nanosheets observed in this study could be explained by the promotion of H + adsorption and H 2 desorption on the oxyhydroxide surface and their high electrical conductivity.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…This value was larger than that for the (Pt/C)/NF electrode (60 mV), but lower than those for previously reported bifunctional catalysts, including NiFe LDH (210 mV), NiFe LDH@graphene (300 mV), Ni 5 Fe LDH (133 mV), CoO/MoO x (163 mV), sulfur‐incorporated NiFe 2 O 4 (138 mV), Ni@NiO (153 mV), and Ni 0.75 Fe 0.25 LDH (169 mV) in 1 m KOH or NaOH (Figure E). A Tafel slope of the FeCoOOH nanosheets (79 mV/dec) was larger than that of the Pt/C catalyst (44 mV/dec) (Figure F), but smaller than reported values for NiFe LDH@graphene (110 mV/dec), Ni 5 Fe LDH (89 mV/dec), and Ni@NiO (84 mV/dec) . The high HER activity of the FeCoOOH nanosheets observed in this study could be explained by the promotion of H + adsorption and H 2 desorption on the oxyhydroxide surface and their high electrical conductivity.…”
Section: Resultscontrasting
confidence: 58%
“…The OER activity is largely affected by the binding energies of the OER intermediates, that is, OH, O, and OOH on the surface of a catalyst . A recent study has shown that the OER activity of CoOOH can be enhanced by doping with Fe atoms, which results in the improvement in the energetics of the OER intermediates . In addition, the direct growth of the FeCoOOH nanosheet arrays supported on the NF ensures a strong bonding between the FeCoOOH nanosheets and NF, which improve the electrical conductivity .…”
Section: Resultsmentioning
confidence: 99%
“…The electrocatalytic water splitting has been considered as a promising approach for sustainable hydrogen production from clean and abundant water with zero carbon emission [4]. The theoretical cell voltage for water splitting is 1.23 V at 298 K (ΔE 0 rev,298 =1.23 V) [5,6]. However, a large overpotential is required to overcome the kinetic barrier induced by the high activation energy, and thus to form the reaction intermediates in the system, whatever for an anodic oxygen evolution reaction (OER) and a cathodic hydrogen evolution reaction (HER) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The lower overpotentials and Tafel slopes of Zn 1‐ x Fe x –LDH/Ni‐foam and Zn 1‐ x Fe x –oxyselenide/Ni‐foam electrodes compared to the other recently reported materials signify that Fe‐cationic as well as Se‐anionic regulated materials with unique ultrathin nanosheet‐like morphologies are functioning as efficient OER catalysts as an anode for alkaline water electrolysis. Previous experimental and theoretical studies showed that the Fe‐doping in the Ni‐ and cobalt‐based ‐LDH and oxyhydroxides played a prominent role for increasing OER . Thus, Fe incorporation in the Zn 1‐ x Fe x –LDH/Ni‐foam and Zn 1‐ x Fe x –oxyselenide/Ni‐foam electrodes enhances the conductivity and provides many active sites for higher OER activity.…”
Section: Resultsmentioning
confidence: 97%